The Effect of Six Weeks of Core Stability Training on Balance and Performance Improvement Among Male Taekwondo Athletes - Ebrahim Ebrahimi; Somayeh Mozafari (Biyumikānīk-i varzishī)
Objective Taekwondo is an Olympic combat sport that demands skills such as jumping and quick directional changes. Core stability exercises may be an effective method to enhance the performance of taekwondo athletes. Therefore, the purpose of this research is to examine the effects of six weeks of core stability exercises on improving balance and performance in male taekwondo practitioners. Methods This quasi-experimental field study involved 30 male taekwondo athletes aged 10-15 from Mashhad city. Participants were selected based on judgment sampling and randomly divided into two groups of 15 each. The single-hop test and triple-hop test were used to assess performance, while the Y balance test evaluated balance. Pre-tests were conducted to measure the research variables before implementing a six-week core stability exercise program for the experimental group. After the training period, post-tests were administered using the same procedures as the pre-tests. Results The findings indicated that completing six weeks of core stability training significantly improved dynamic balance in the medial-posterior direction (P=0.021) and overall performance (P=0.002) in the experimental group compared to the control group. Conclusion Core stability exercises can help reduce injuries and enhance athletic performance. This study aimed to investigate the impact of six weeks of core stability exercises on the balance and performance of young male taekwondo athletes. The results suggest that core stability exercises effectively improve both balance and performance in taekwondo practitioners, leading to enhanced athletic performance.